2005
DOI: 10.1021/np050109q
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Phenylpropanoid Glycosides from the Stems of Smilax china

Abstract: Bioassay-guided fractionation of an ethanol extract of Smilax china led to the isolation of nine phenylpropanoids including six new compounds, smilasides A-F (1-6), and three known phenylpropanoids, smiglaside E, heloniosides B, and 2',6'-diacetyl-3,6-diferuloylsucrose. Structural elucidation of isolates 1-6 was based on spectroscopic data analysis. These new phenylpropanoids were evaluated against several human tumor cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 5 publications
1
25
0
1
Order By: Relevance
“…By using bioassay-guided fractionation together with repeated chromatographic and spectroscopic methods, 13 6.12) were in good accordance with three pairs of trans-olefinic protons in the R, -unsaturated carbonyl systems of the feruloyl units in 1. 14,15 The 1 H and 13 C NMR spectrum (Tables 1 and 2) of 1 showed an R-anomeric resonance at δ H 5.53 with a small coupling constant (d, J ) 3.6 Hz, H-1′) due to a gauche conformation, according to the Karplus relation, 16 together with 12 oxygenated carbon signals at δ C 62.4-105.8. These data implied that 1 is a disaccharide containing both a pentose and a hexose moiety.…”
Section: Resultsmentioning
confidence: 96%
“…By using bioassay-guided fractionation together with repeated chromatographic and spectroscopic methods, 13 6.12) were in good accordance with three pairs of trans-olefinic protons in the R, -unsaturated carbonyl systems of the feruloyl units in 1. 14,15 The 1 H and 13 C NMR spectrum (Tables 1 and 2) of 1 showed an R-anomeric resonance at δ H 5.53 with a small coupling constant (d, J ) 3.6 Hz, H-1′) due to a gauche conformation, according to the Karplus relation, 16 together with 12 oxygenated carbon signals at δ C 62.4-105.8. These data implied that 1 is a disaccharide containing both a pentose and a hexose moiety.…”
Section: Resultsmentioning
confidence: 96%
“…e; Table S4). These two metabolites were previously identified as smilaside A (3,6 diferuloyl‐3′,6′‐diacetylsucrose) in Smilax china (Kuo et al ., ) and smiglaside C (3,6 ‐ diferuloyl‐2′,3′,6′‐triacetylsucrose) in Smilax glabra (Chen et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…However, many Smilax species from other parts of the world such as Smilax china have been submitted to numerous chemical and biological studies due to their interesting properties. These species have been shown to contain steroidal saponins and phenolic compounds Sashida et al, 1992;Bernardo et al, 1996;Shu et al, 2002;Sautour et al, 2006;Xu et al, 2006) and have demonstrated interesting anti-inflammatory, anti-conceptive, cytotoxic, antioxidant, immunomodulatory, anticancer, hypoglycaemic, uricosuric and antifungal activities (Giachetti et al, 1988;Suh et al, 1996;Fukunaga et al, 1997;Lee et al, 2001;Jiang and Xu, 2003;Cox et al, 2005;Kuo et al, 2005;Sautour et al, 2005;Thabrew et al, 2005;Xu et al, 2005;Chu and Ng, 2006;Huang et al, 2006;Wang et al, 2006;Li et al, 2007).…”
Section: Introductionmentioning
confidence: 99%